The Major Metaphors of Evolution Darwinism Then and Now - Agosta, Salvatore J.; Brooks, Daniel R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book presents a unified evolutionary framework based on three sets of metaphors that will help to consolidate discussions on evolutionary transitions. Evolution is the unifying principle of life, making identifying ways to apply evolutionary principles to tackle existence-threatening crises such as climate change crucial. A more cohesive evolutionary framework will further the discussions in this regard and also accelerate the process itself. This book lays out a framework based on three dualistic classes of metaphors - time, space, and conflict resolution. Evolutionary transitions theory shows how metaphors can help us understand selective diversification, as Darwin described with his "tree of life". Moreover, the recently proposed Stockholm paradigm demonstrates how metaphors can help shed light on the emergence of complex ecosystems that Darwin highlighted with his "tangled bank" metaphor. Taken together, these ideas offer proactive measures for coping with existential crises for humanity, such as climate change. The book will appeal to biologists, philosophers and historians alike.
Chapter 1: Context -- Chapter 2: A Talking Book -- Chapter 3: Setting the Stage -- Chapter 4: Neo-Darwinism, Expansion and Consolidation (1900-1980) -- Chapter 5: Criticism, Resistance, a Glimmer of Hope -- Chapter 6: Buying Time -- Chapter 7: Making Space -- Chapter 8: Conflict Resolution -- Chapter 9: Evolutionary Transitions -- Chapter 10: The Stockholm Paradigm -- Chapter 11: Putting Evolution to Work.
Keywords: Evolutionary biology; Biology-History.; Philosophy and science; Evolutionary Biology; History of Biology; Philosophy of Science